Association of the waist-hip ratio with plasma adiponectin related to coronary artery disease (Bangladesh Journal of Medical Science, 2018)
Objective: By enrolling a prospective study of 82 patients that underwent non-urgent coronary angiography for coronary artery disease (CAD), it is aimed to investigate the correlation between adiponectin and waist-hip-ratio with severity of CAD.Materials and methods: The results of the angiography, divided the patients into two groups, patients admitted with a diagnosis of CAD and non-CAD. In the conducted hospital based research, two groups were involved: the study group with documented angiographically CAD and control group without angiographic evidence of CAD. Some of the baseline adiponectin levels in stored serum samples of all patients, anthropometric and biochemical risk factors were assessed in both groups.Result and discussion: As the result, we have seen the presence of CAD that was associated with current smoking, male gender, waist–hip ratio (WHR).While, no significant difference between median adiponectin levels at baseline were observed between cases and controls.Conclusion: There is a significant positive correlation between waist - hip ratio and presence of severity of coronary artery disease.Bangladesh Journal of Medical Science Vol.17(2) 2018 p.290-295